PENGARUH ENVIRONMENT SOCIAL GOVERNANCE, KUALITAS AUDIT, RISIKO BISNIS TERHADAP NILAI PERUSAHAAN DENGAN MANAJEMEN LABA SEBAGAI VARIABEL MODERASI (STUDI PADA PERUSAHAAN INDEKS ESG LEADERS YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Putri Balqis Sarah Dwipa; Mukhtaruddin Mukhtaruddin; Ika Sasti Ferina (ITB AAS Indonesia Surakarta, 2024)
The study aims to examine and analyze the effect of environmental social governance (ESG), audit quality, and business risk on firm value, with earnings management as a moderating variable. The population of this research is companies listed on the Indonesia Stock Exchange and indexed ESG Leaders for the period 2018–2022. Based on the sampling method with purposive samplings in the study period of five years, 20 companies or 100 observation data were obtained. Data collection uses documentation techniques collected from sustainability reports and annual reports. The analysis technique is moderated regression analysis (MRA). The results of this study indicate that ESG disclosure and audit quality have a positive and significant impact on firm value, but business risk has no significant effect on firm value. Earnings management is able to moderate the ESG and audit quality of firm value, but earnings management has not been proven to moderate business risk; rather, it was an independent predictor of moderation that influenced firm value.